Hydrolysis and reconjugation of gibberellin A20 glucosyl ester by seedlings of Zea mays L. - Schneider, G (1992)
The [6-2H]glucosyl ester of [17-13C,3H]gibberellin A20 (GA20) was injected into light-grown 14-day-old seedlings of normal, dwarf-1, and dwarf-5 maize (Zea mays L.). The plant material was extracted 24 h later, and the extracts were purified by solvent partitioning, column chromatography, and HPLC. 13C-labeled metabolites were identified from the purified extracts by full-scan gas chromatography/mass spectrometry and selected ion current monitoring in conjunction with Kovats retention indices. The metabolites, [13C]GA20, [13C]GA29, [13C]GA20-13-O-glucoside, and [13C]GA29-2-O-glucoside, were identified from normal, dwarf-1, and dwarf-5 seedlings. [13C]GA8 and [13C]GA8-2-O-glucoside were also identified from normal and dwarf-5 seedlings but not from dwarf-1 seedlings. The data provide definitive evidence for the endogenous hydrolysis by the seedlings of the introduced conjugate and its reconjugation to three glucosides.